(-13)*(-2)*½*(-5)=
(-14)*(-0,7)*(-1 3/7)=
(-⅓)*1 1/5*(-12)*(-1/6)=
(-3⅔)*0,3*(-10)*(-6/11)=
(-6/7)*(-4,2)*(-1)*0=
(-100)*3,125*(-1 1/7)*(-1/25)=

(-4)*0,5*(-3)*(-(-5))=
½*(-⅓)*10*(-12)*(-13)=
(-0,38)*(-12)*(-0,12)*1=
(-13)*(-1,2)*(-1,1)*(-1,3)=
(-⅔)*(-5)*(-3)*4=
¾*(-1)*0,5*(-10)*(-½)=

Bardzo proszę o pomoc ;))
Za dobre wyniki daje najlepsze ;))

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-13T20:58:56+01:00
(-13)*(-2)*½*(-5)=26*0,5*(-5) = -65

(-4)*0,5*(-3)*(-(-5))= chyba 30
(-0,38)*(-12)*(-0,12)*1= - 0,5472
(-13)*(-1,2)*(-1,1)*(-1,3)=22,308
¾*(-1)*0,5*(-10)*(-½)= 0,75 *(-1)*0,5*(-10)*(-0,5) = - 1,875
2009-12-13T21:02:23+01:00
-65
-14
-0,8
-6
0
-5000/350



30
7
-0,5472
22,308
-40
1,875